The Magnitude of Celebrity Endorser in Terms of Influencing Followers Trust of Product in Instagram - Gemerlang Adhityatama; Anita Maharani (Ilomata International Journal of Management, 2023)
Instagram is considered as one of powerful social media that enable its user to promote and influence products and or services since the beginning of its existence. Then, the celebrity endorser act as influencer sometimes paid and or unpaid for products and or services. This research seeks the understanding how far could celebrity endorser affect Instagram users to trust products and or service offered by business. Studies found electronic words of mouth practiced within celebrity endorser, but limited studies raise issues between physical attractiveness and social attractiveness within electronic words of mouth with parasocial interaction, therefore specific literatures were elaborated to form research model. This research involves Instagram active users, with no specific locations but have interest in one Celebrity name Anya Geraldine, and Partial Least Square was used to assess the research model while respondents involved in this research were 115 person. After collecting data for one-month from 1st January 2023 to 1st February 2023 we may assess our hypothesis. This research conclude two factors are not supported, that are physical attractiveness and parasocial interactions.